Image Traces in the Rhyme of Ajaj - Yacoub, Abdul Karim; Mahmoud, Rama Hassan (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The traces of the image within the construction of the rhyme have shown the psychological and semantic functions, exceeded the physical space determined by the sense of sight, using the technical technique of the image in the presentation of the poetic state, and desires according to its start, and formative stops, which generated visual traces stemming from both emotional and intellectual basis. The image has come into a descriptive space, taken from a corresponding pattern and, in some cases, a synchronic pattern that has made Ajaj a pillar of silent dialogue, with only his voice pointing to the other (described). Al-Ajaj worked on monitoring the particles, their affective characteristics in the characters of the event, and the emotional tension created by the formulas, which is a gap in the image formation through the analogous structure in it, and then moving to the semantic charge contained in the image.